2021
DOI: 10.1159/000519886
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Drug-Related Community Impacts of Open Drug Scenes: A Scoping Review

Abstract: <b><i>Introduction:</i></b> Places where people deal and/or use drugs publicly are known as open drug scenes (ODSs). Drug-related community impacts (DRCIs) refer to drug-related issues that negatively influence public and individual health, communities, businesses, and recreational and public space enjoyment. There are no well-established criteria for identification of DRCIs. We therefore performed a scoping review of literature to determine DRCIs indicators associated with ODSs. <b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
(167 reference statements)
0
10
0
Order By: Relevance
“…In communities around the world, the COVID-19 pandemic laid bare underlying social inequities [40], and as reiterated by our findings, these inequities had notable consequences for the wellbeing of PWUD and their treatment experiences. First, for PWUD experiencing socioeconomic marginalization or unemployment, financial instability can not only jeopardize their material security, but also impact substance use patterns, drug scene involvement, and exposure to overdose risks, criminalization, or violence [41][42][43]. Second, COVID-19 threatened the physical health of iOAT clients, and ongoing research has demonstrated how substance use and comorbidities position PWUD for greater risk of severe COVID-19 outcomes [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In communities around the world, the COVID-19 pandemic laid bare underlying social inequities [40], and as reiterated by our findings, these inequities had notable consequences for the wellbeing of PWUD and their treatment experiences. First, for PWUD experiencing socioeconomic marginalization or unemployment, financial instability can not only jeopardize their material security, but also impact substance use patterns, drug scene involvement, and exposure to overdose risks, criminalization, or violence [41][42][43]. Second, COVID-19 threatened the physical health of iOAT clients, and ongoing research has demonstrated how substance use and comorbidities position PWUD for greater risk of severe COVID-19 outcomes [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In communities around the world, the COVID-19 pandemic laid bare underlying social inequities [39], and as reiterated by our ndings, these inequities had notable consequences for the wellbeing of PWUD and their treatment experiences. First, for PWUD experiencing socioeconomic marginalization or unemployment, nancial instability can not only jeopardize their material security, but also impact substance use patterns, drug scene involvement, and exposure to overdose risks, criminalization, or violence [40][41][42]. Second, COVID-19 threatened the physical health of iOAT clients, and ongoing research has demonstrated how substance use and comorbidities position PWUD for greater risk of severe COVID-19 outcomes [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals’ motivations to participate may be linked to their own experiences of substance use and treatment (or lack thereof) or a desire to reduce socioeconomic vulnerability that commonly accompanies high-intensity substance use (Richardson et al, 2015; Timmermans & McKay, 2009). Barriers to participation may be a function of reluctance to engage produced by strong social integration in drug use scenes (Saberi Zafarghandi et al, 2021) or negative interactions with surveillance from wide-ranging institutions (Brayne, 2014). Willingness to participate may be predominantly shaped by institutional interactions supportive of enrollment, such as positive interactions with healthcare professionals or social services (Friedmann et al, 2003).…”
Section: Methodsmentioning
confidence: 99%